The effect of developmental stages of corm, type of medium and plant growth regulators in callus induction of Crocus sativus L. - Seyed Mahdi Ziaratnia (University of Birjand, 2021)
Purpose: The efficiency of callus induction as source of bioactive compound is a critical step in the cell suspension culture for commercial production of important secondary metabolites. One of the main factors affecting callus efficiency is the developmental stage of explants. On the other hands, it has been declared that the optimization of medium composition has a significant influence on callogenesis and increment of biomass.  Research method: The aim of this study was the evaluation of different developmental stages of saffron corms as a source of explant preparation (immature and mature corms), plant growth regulators (PGRs) combinations (1-Naphthaleneacetic acid (NAA); 2, 4-dichlorophenoxyacetic acid (2,4-D); 6-Benzyladenine (BA) and kinetin (Kin)) and type of medium (Gamborg (B5) medium and Murashige and Skoog (MS) medium) in callus induction in saffron corms to increase cell biomass. The media were supplemented with different combinations of 1-Naphthaleneacetic acid or 2, 4-dichlorophenoxyacetic acid (2, 4, 8 mgL-1) as auxins and 6-Benzyladenine or kinetin (1, 4, 8 mgL-1) as cytokinin. Findings: The results showed that mature corms harvested in May had the best developmental stage for callogenesis. The maximum callus formation was recorded in B5 medium supplemented with 2,4-dichlorophenoxyacetic acid (4 mgL-1) and kinetin (1 mgL-1) with 2.61 g fresh weight. Limitations: No limitations to report. Originality/Value: This protocol for sampling explant and callus formation was found to make suitable sources of plant material for further study in production of bioactive compounds via cell suspension cultures.